Indicadores de sustentabilidade e atitudes ambientais como ferramentas de suporte à tomada de decisão em zonas especiais de interesse social: o caso da comunidade São Luís, João Pessoa-PB - Cesar, Igor de Vasconcellos (2015)
The present paper has as a goal a social environmental diagnosis at São Luís ZEIS, a Social Interest Particular Zone, situated at Bessa neighborhood in João Pessoa, PB. These Particular Zones correspond to a new legal capability, rose in Brazil of the 80's because of the increased popular pressure which claimed for housing as well as an attempt to foment the programs of urban reform established by the 1988 constitution. Under a view of sustainability as well as the environmental perception, the research took direction towards the construction of basis and possibilities which can lead to a implementation of public policies that prioritize environmental quality improvements and then the human being's way of life and welfare. It was chosen the sustainability panel method to compound the indicators of the community studied, coupling the local residents attitudinal aspects and features through measurement of their inserts in the New Ecological Paradigm (NEP).